VOMITING IS A POTENTIAL ADVERSE DRUG REACTION FOR LEVOMILNACIPRAN (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Levomilnacipran is a drug used to treat depression. Micro Labs is a generic drug company which had developed an extended release formulation of Levomilnacipran 120 mg capsule. Two studies were conducted to assess the safety, tolerability and bioequivalence of the extended release formulation of 120 mg Levomilnacipran capsules. A total of 42 subjects had been included for each of the fasting and fed studies. Out of them, 30 subjects completed the fasting study and 28 subjects completed the fed study. Pharmacokinetic parameters like Cmax, AUC0-t, AUC0-inf, Tmax, Kel, t1/2 and %AUCextra were calculated for Levomilnacipran in order to compare the bioavailability of the test and reference formulations. The studies were conducted in healthy human volunteers in both fasting and fed conditions as per the US regulatory requirements for conduct of bioequivalence studies. The formulations were found to be bioequivalent to each other. Vomiting was observed as a major adverse reaction.